2019
DOI: 10.1002/er.5014
|View full text |Cite
|
Sign up to set email alerts
|

Constructing 1D/2D heterojunction photocatalyst from FeSe 2 nanorods and MoSe 2 nanoplates with high photocatalytic and photoelectrochemical performance

Abstract: Although the traditional metal oxide catalyst has high activity and strong degradation ability, the forbidden bandgap is generally larger, and the utilization rate of sunlight is much low. Moreover, the high internal resistance inhibits carrier transfer, so the photoelectrochemical performance needs to be improved. Selenides with narrow bandgap and low internal resistance are promising candidates for photocatalysts. A new type of 1D/2D selenide heterojunction was constructed by compositing MoSe 2 and FeSe 2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 68 publications
(136 reference statements)
0
13
0
Order By: Relevance
“…The TEM image in Figure 7i shows the interface contact between MoSe 2 and FeSe 2 having a d spacing of 0.646 nm attributed to the (002) plane and FeSe 2 having a d spacing of 0.368 nm corresponding to the (110) lattice plane. 78 Similarly, Wu et al reported the self-assembly preparation of hybrid Pdoped g-C 3 N 4 tubes through the bottom-up approach of pyrolysis shown in Figure 7j under the desired condition. The product was then freeze-dried and calcined for growth of the nanostructure.…”
Section: Synthesis Of 1d/2d Photocatalystsmentioning
confidence: 90%
“…The TEM image in Figure 7i shows the interface contact between MoSe 2 and FeSe 2 having a d spacing of 0.646 nm attributed to the (002) plane and FeSe 2 having a d spacing of 0.368 nm corresponding to the (110) lattice plane. 78 Similarly, Wu et al reported the self-assembly preparation of hybrid Pdoped g-C 3 N 4 tubes through the bottom-up approach of pyrolysis shown in Figure 7j under the desired condition. The product was then freeze-dried and calcined for growth of the nanostructure.…”
Section: Synthesis Of 1d/2d Photocatalystsmentioning
confidence: 90%
“…Zhang and coworkers reported a new type of 1D/2D selenide heterojunction constructed by compositing MoSe 2 nanoplates and FeSe 2 nanorods, two kinds of narrow bandgap metal selenides as shown in Figure 3c. [ 48 ] In the FeSe 2 /MoSe 2 1D/2D heterostructure, FeSe 2 1D nanorods loaded on the 2D surface of MoSe 2 nanoplates to achieve a large surface well contacting for carriers′ transfer channel, and mostly carriers generated in the FeSe 2 will transfer through the channel, which means carriers can transfer between the heterojunction very easily to achieve high separation efficiency and enhanced photocatalytic performance in the degradation of methylene blue (MB) as shown in Figure 3d. Besides, a series of direct Z‐scheme WO 2.72 /ZnIn 2 S 4 hybrid photocatalysts composed of 1D WO 2.72 nanorods and 2D ZnIn 2 S 4 nanosheets also have been designed and constructed for tetracycline hydrochloride (TCH) degradation.…”
Section: Growth Of 1d Nanotubes/nanowires On 2d Nanomaterialsmentioning
confidence: 99%
“…Reproduced with permission. [ 48 ] Copyright 2019, John Wiley & Sons; e,f) CdS/Ti 3 C 2 T x heterostructure. Reproduced with permission.…”
Section: Growth Of 1d Nanotubes/nanowires On 2d Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a typical 2D graphene-layered material, transition metal dihalide (TMD) has great potential in the application of photoelectric conversion due to its quantum confinement effect, inherent atomic structure, and fascinating physical properties. [7][8][9] To date, various TMD-based photodetectors have been reported in previous studies and have shown excellent performance. For example, Zheng et al prepared a large-area, highcrystalline WSe 2 thin film by pulsed laser deposition and applied it to a broadband photodetector of 370-1064 nm.…”
Section: Introductionmentioning
confidence: 99%